Gender differences in rice production participation among smallholder farmers in small-scale irrigation schemes in mbarali district, Tanzania - Neema Mwalyagile; John N. Jeckoniah; Raymond J. Salanga (Journal of Agriculture and Food Research)
Smallholder farmers are crucial to agri-food production in sub-Saharan Africa. However, gender disparities in rice production participation persist in Tanzania. Existing research has yet to fully explore how demographic and socioeconomic factors influence gendered participation in rice production. This study assesses gender differences in rice production participation patterns among smallholder farmers and identify gender-related socio-economic and demographic factors influencing differences in participation within small-scale irrigation schemes in Mbarali District. Using cross-sectional approach, data were collected from 397 randomly selected farmers through structured questionnaire and analyzed with descriptive and inferential statistics, including ordered probit regression. The results revealed significant gender differences in rice production participation (p < 0.01). Male farmers had higher participation rates in activities such as land preparation, seedbed preparation, seedling management, irrigation, herbicide, fertilizer, pesticide application, harvesting, transporting, storage, and selling, while female farmers had higher participation rates in transplanting and weeding. The overall level of participation was moderate, with 78 % of male farmers and 49 % of female farmers. However, larger proportion of females (43 %) were at a lower participation levels compared to only 1 % of male farmers, while 21 % of males and 8 % of females were at high participation levels. Factors like household size, farming management, hierarchical position within households, decision-making power, and the ability to access irrigation water positively influenced participation levels, while land size cultivated had a negative impact (p < 0.05). These were gender-related socio-economic and demographic factors that disadvantage female farmers' participation (p < 0.05). While the age of the farmer and inadequacy of irrigation water significantly affected participation levels, farm-hired labour had positive influence, however, these factors were not gender-specific. The study concludes that gender differences in participation in rice production are influenced by demographic and socio-economic factors. To address these, the study recommends for interventions that reduce gender disparities by promoting equality in resource access, enhancing women's decision-making power over resources and ability to access irrigation water, and ensure sufficient water in small-scale irrigation schemes. The government should create an enabling environment that supporting female farmers in small-scale irrigation schemes for broader gender equality in agriculture and rural development.